Wellbeing Assessment Yardstick: Evidence from the Elderly Wellbeing across Russian Subnational Macro-Regions - Pavlova I. A. Irina Anatolievna; Monastyrny E. A. Evgeny Aleksandrovich; Gumennikov I. V. Iliya Vladimirovich; Golubeva E. Yu. Elena Yurjevna (2019, 2019)
Title screen